2015
DOI: 10.1093/ntr/ntv078
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between E-Cigarette Type, Frequency of Use, and Quitting Smoking: Findings From a Longitudinal Online Panel Survey in Great Britain

Abstract: Introduction:E-cigarettes can be categorized into two basic types, (1) cigalikes, that are disposable or use pre-filled cartridges and (2) tanks, that can be refilled with liquids. The aims of this study were to examine: (1) predictors of using the two e-cigarette types, and (2) the association between type used, frequency of use (daily vs. non-daily vs. no use), and quitting.Methods:Online longitudinal survey of smokers in Great Britain was first conducted in November 2012. Of 4064 respondents meeting inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
265
5
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(289 citation statements)
references
References 36 publications
(46 reference statements)
17
265
5
2
Order By: Relevance
“…Much of the difficulty in establishing a benefit for e‐cigarettes has do with the scarcity of randomized control trials demonstrating a benefit for e‐cigarettes as cessation aids, although the studies available do suggest a benefit 16, 17. Data from observational studies appear to support a benefit of e‐cigarettes for smoking cessation, but are more difficult to interpret because of selection biases, variations in the types of e‐cigarettes used by smokers, and variability in the patterns of use of e‐cigarettes (eg, daily versus less than daily) 1, 2, 3, 4, 18. Carefully designed studies are needed to conclusively determine the efficacy of e‐cigarettes for long term smoking cessation and to identify individuals most likely to benefit from e‐cigarettes as a cessation aid and those products which are most effective.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the difficulty in establishing a benefit for e‐cigarettes has do with the scarcity of randomized control trials demonstrating a benefit for e‐cigarettes as cessation aids, although the studies available do suggest a benefit 16, 17. Data from observational studies appear to support a benefit of e‐cigarettes for smoking cessation, but are more difficult to interpret because of selection biases, variations in the types of e‐cigarettes used by smokers, and variability in the patterns of use of e‐cigarettes (eg, daily versus less than daily) 1, 2, 3, 4, 18. Carefully designed studies are needed to conclusively determine the efficacy of e‐cigarettes for long term smoking cessation and to identify individuals most likely to benefit from e‐cigarettes as a cessation aid and those products which are most effective.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the review did not take into account frequency and duration of the use of e-cigarettes; studies have shown that greater frequency and duration (ie, daily use for at least a month) is associated with a greater likelihood of quitting. 17,18 Third, the review treated all ECs the same, despite the many dimensions on which these products vary, including dimensions related to potential nicotine delivery; a recent study has shown that tank systems were associated with greater likelihood of quitting, relative to other types of e-cigarettes (eg, cigalikes, disposables). 13 It is presently unclear whether the use of ECs is associated with greater cigarette abstinence than current practice (ie, use of nicotine replacement therapy [NRT], prescription medications [PM] or behavioral therapy) as the majority of the studies to date have not included a comparison to either currently approved quitting methods (eg, NRT, PM) or no EC use.…”
Section: Introductionmentioning
confidence: 99%
“…All have been criticized for including non-daily users in their analyses, but the most recent study which separated daily from non-daily users also found no statistically significantly differences between daily, less than daily and non-vaping smokers for smoking cessation [9]. A sub-analysis found that daily 'tank' vapers were more likely to quit, although nearly three quarters of these were still dual using at 12 months and the proportions of smokers involved were small [10]. So the new emperor's clothes of ENDS in smoking cessation are looking decidedly threadbare.…”
mentioning
confidence: 99%